Implementation of general classical force field and their applicability for simple organic systems - Gallegos Estrada, Carlos Francisco (2024)
Computational chemistry is crucial in scientific research and industry for understanding molecular structure and interactions. However, its effectiveness depends on factors like computational cost and accuracy. Quantum mechanical (QM) methods offer high accuracy but are computationally demanding, especially for larger systems where costs escalate sharply. General Force Fields (FF), like Dreiding and Universal Force Field (UFF), are well known for their efficiency within computational chemistry. These force fields offer cost-effective solutions, making them highly advantageous for the study of big atomic systems. Their ability to provide accurate representations of molecular interactions allows researchers to extract valuable insights at reasonable calculation times, contributing significantly to our understanding of chemical phenomena. The integration of cost-effective computational methods with widely used simulation environments is crucial for advancing research accessibility, specially in developing countries where access to powerful computing resources is limited. This work presents the implementation and performance assessment of the Dreiding and UFF in computational chemistry calculations. The primary objective was to integrate the Dreiding force field into the structure2lammps package, complementing the existing implementation of UFF, to enable compatibility with the Atomic Simulation Environment (ASE) and the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS). This integration aimed to ensure robustness by subjecting the implementation to thorough testing procedures. Extensive testing across various applications, including molecular relaxation, energy calculations, and mechanical modeling, confirmed the reliability and effectiveness of these force fields in atomic interaction calculations. Their performance was validated through comparisons with literature references of more sophisticated computational methods and Density Functional Tight Binding (DFTB) calculations. Both force fields demonstrated reasonable precision in modeling the geometric characteristics of simple molecules. Dreiding and UFF effectively captured the isomerization energies of a set of organic molecules. Additionally, the study investigated the equation of state fitting for bulk modulus calculations. The retrieved data shows good agreement when compared to observations in DFTB calculations and data from the literature.